PENGARUH BAURAN PEMASARAN TERHADAP MINAT BELI KONSUMEN MINYAK GORENG KUNCI MAS PADA PT. SARIMEKAR CAHAYA PERSADA SAMPIT - Guruh Fajar Alamsyah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study attempts to explain the assumption that the marketing mix (product, price, place and promotion) has an influence on consumer buying interest in Kunci Mas Cooking Oil at PT. Sarimekar Cahaya Persada Sampit. In this study, the distribution of the questionnaire was 80 copies, which deserved to be used as research samples were 80 respondents. To obtain data, the researcher used a questionnaire distributed to consumers of PT. Sarimekar Cahaya Persada Sampit. While the technical analysis of the data using the validity test, the reliability of the research instrument and the research hypothesis test. From the results, the coefficient value of R Square (r2) is 61.2% while the remaining 38.8% is influenced by other variables outside the research variables. Mas At PT. Sarimekar Cahaya Persada . This is evidenced by the value of tcount > ttable (3.657 > 1.99210) with a significant level of 0.000 <0.05. This means that there is a significant influence between products on consumer buying interest. For the t-test of the price variable (X2) that there is a price effect on consumer buying interest in Kunci Mas Cooking Oil at PT. Sarimekar Cahaya Persada Sampit. This is evidenced by the value of tcount > ttable (5.516 > 1.99210) with a significant level of 0.000 <0.05. This means that there is a significant influence between price on consumer buying interest. For the t-test of the Place variable (X3) that there is an Influence of Place on Consumer Purchase Interest of Kunci Mas Cooking Oil at PT. Sarimekar Cahaya Persada Sampit. This is evidenced by the value of tcount > ttable (2.729 > 1.99210) with a significant level of 0.008 < 0.05. This means that there is a significant influence between Place on Consumer Purchase Interest and the t-test of the Promotional variable (X4) shows that there is a Promotion Effect on Consumer Purchase Interest of Kunci Mas Cooking Oil at PT. Sarimekar Cahaya Persada Sampit. This is evidenced by the value of tcount > ttable (3.276 > 1.99210) with a significant level of 0.002 < 0.05. This means that there is a significant influence between promotions on consumer buying interest. Based on the F (simultaneous) test, it shows that there is an effect of product, price, place and promotion on the consumer buying interest of Kunci Mas Gireng Oil at PT. Sarimekar Cahaya Persada Sampit. This is evidenced by the value of fcount > ftable (29.597 > 2.49) with a significant level of 0.000 < 0.05. Based on the correlation analysis, the R number of 0.782 indicates that there is a fairly strong relationship between Product, Price, Place and Promotion that affect Consumer Purchase Interest of Kunci Mas Gireng Oil at PT. Sarimekar Cahaya Persada Sampit.